2001
DOI: 10.1097/00002060-200102000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Admission Functional Status on Functional Change After Stroke Rehabilitation

Abstract: The functional levels of affected patients at admission stratified by the FIM scale roughly predict the degree of functional gain after rehabilitation in survivors with a first episode of ischemic stroke. Moderately affected patients will benefit from intensive rehabilitation. These findings may be useful for rehabilitation triage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 17 publications
5
29
0
Order By: Relevance
“…11,16 The FIM has established content and construct validity, sensitivity, and interrater reliability for stroke. 10,14,15 Motor items are categorized into eating, grooming, bathing, dressing, toileting, continence, transfers, and mobility domains. Cognitive items assessed include communication, social interaction, problem solving, and memory.…”
Section: Editor's Notementioning
confidence: 99%
See 2 more Smart Citations
“…11,16 The FIM has established content and construct validity, sensitivity, and interrater reliability for stroke. 10,14,15 Motor items are categorized into eating, grooming, bathing, dressing, toileting, continence, transfers, and mobility domains. Cognitive items assessed include communication, social interaction, problem solving, and memory.…”
Section: Editor's Notementioning
confidence: 99%
“…3,7,9 Stroke rehabilitation improves outcomes. 10,11 However, negative perceptions in recurrent stroke may lead clinicians to withhold intensive and comprehensive rehabilitation services which is detrimental to recovery. 2,5 Knowledge of these functional and related efficiency outcomes will facilitate optimization of rehabilitation interventions and resources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 The main objective is measure quantitatively what the patient with the disability can accomplish. It can also provide consistent data to follow up the patient functional degree from the beginning of rehabilitation, until and after the discharge, 10,11 and to evaluate the effectiveness of the therapeutic approach. 12 However, since 2001, with the approval of the International Classification of Functionality, Disability and Health (ICF) by the World Health Organization (WHO), the understanding of human functioning and disability came to identify not only consequences of diseases, but the unimpaired aspects of the body and those activities and participations with or without problems, together with the environmental and personal characteristics that affect the human experience.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that impairment on admission could predict both Functional Independence Measure (FIM) raw scores 1) and activities of daily living (ADL) scores on discharge [2][3][4][5] . Moreover, comorbidities and complications were predictive factors of ADL scores on discharge 6) .…”
Section: Introductionmentioning
confidence: 99%